Composite body construction optimization and technological design of an electrically powered race car - Rafał Chatys; Kacper Kuta; Alexander Panich (Advances in Mechanical and Materials Engineering, 2018)
The paper discusses the ways of structural optimization of composite automotive bodies, such as in race cars using electric and hybrid power sources. To reach these goals we were using CFD aerodynamic design check. Taking into account all the above mentioned issues, the integrated 3D-CAD race bolide body model prototype was designed, based on the concept of NACA profiles used in surface positive and negative curvatures generation to ensure better air overflow, stability, drag coefficient, downforce etc. The result of the integrated 3D-CAD race bolide body model is also presented as a real scale composite automotive body. This paper also discusses technological methods as well as problems and stages of real-life designing (from mould to ready composite part). The results can be useful for such consideration and on such issues as production and development of complex shape composite bodies, using readily obtainable and justified by cost-effectiveness materials and software.